2015
DOI: 10.1002/cne.23801
|View full text |Cite
|
Sign up to set email alerts
|

S‐phase duration is the main target of cell cycle regulation in neural progenitors of developing ferret neocortex

Abstract: The evolutionary expansion of the neocortex primarily reflects increases in abundance and proliferative capacity of cortical progenitors and in the length of the neurogenic period during development. Cell cycle parameters of neocortical progenitors are an important determinant of cortical development. The ferret (Mustela putorius furo), a gyrencephalic mammal, has gained increasing importance as a model for studying corticogenesis. Here, we have studied the abundance, proliferation, and cell cycle parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
(134 reference statements)
3
45
1
Order By: Relevance
“…Interestingly, similar changes in cell cycle have been observed in Axolotls, suggesting that it might be a general principle of spinal cord regeneration [8,21]. It has been suggested that long S phase might be necessary for progenitors undergoing selfrenewal division to ensure genome integrity, especially in response to high level of ROS present in the nervous system [22][23][24]. The regenerating tail is an oxidative environment and we show here that foxm1 expression requires ROS.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, similar changes in cell cycle have been observed in Axolotls, suggesting that it might be a general principle of spinal cord regeneration [8,21]. It has been suggested that long S phase might be necessary for progenitors undergoing selfrenewal division to ensure genome integrity, especially in response to high level of ROS present in the nervous system [22][23][24]. The regenerating tail is an oxidative environment and we show here that foxm1 expression requires ROS.…”
Section: Discussionsupporting
confidence: 75%
“…The cell cycle length of the dividing cells of the adult rat DG was estimated to be 25h, of which 9.7h was the length of the S‐phase (Cameron & McKay, ). Even if studies on the cell cycle length of the canine neural dividing cells are lacking, the S‐phase length of neural progenitors of non‐human primates and ferrets (gyrencephalic carnivore animals) was found to be less than 24h (Kornack & Rakic, ; Turrero Garcia et al, ), allowing us to infer that the extremely low difference (less than 14h) in the S‐phase length of the carnivore and rodent neural progenitors could affect only the short‐term outcome of the ongoing neurogenesis and could not have any effect in the here long‐term study of the rat and canine BrdU + cell populations.…”
Section: Discussionmentioning
confidence: 98%
“…Current literature proposes a lengthened cell cycle and particularly an extended S‐phase for proliferating neural cells of the gyrencephalic brains as compared to the rodent ones (Turrero Garcia et al, ). The cell cycle length of the dividing cells of the adult rat DG was estimated to be 25h, of which 9.7h was the length of the S‐phase (Cameron & McKay, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, overexpression of TRNP1 selectively increases aRG (and not bIPs), which results in tangential expansion of neocortex without gyrus formation . In ferrets, proliferating bRGs have a longer cell cycle duration (including a longer G1 and S phase) compared with the proliferating aRGs, which may result in greater contribution of the former cells to neurogenesis at late developmental stages and account for gyration . Altogether, these data support a critical contribution of intermediate progenitor proliferation to the formation of gyri.…”
Section: Cellular Bases Of Cortical Gyrationmentioning
confidence: 60%